2008
DOI: 10.1104/pp.108.119404
|View full text |Cite
|
Sign up to set email alerts
|

AGL61 Interacts with AGL80 and Is Required for Central Cell Development in Arabidopsis  

Abstract: The central cell of the female gametophyte plays a role in pollen tube guidance and in regulating the initiation of endosperm development. Following fertilization, the central cell gives rise to the seed's endosperm, which nourishes the developing embryo within the seed. The molecular mechanisms controlling specification and differentiation of the central cell are poorly understood. We identified AGL61 in a screen for transcription factor genes expressed in the female gametophyte. AGL61 encodes a Type I MADS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 42 publications
3
125
0
2
Order By: Relevance
“…Relatively few genes have been shown to be required for both central cell identity and fusion of polar nuclei, e.g. the transcription factors DIANA/AGAMOUS LIKE 61 (DIA/AGL61) and AGL80 (Bemer et al, 2008;Portereiko et al, 2006;Steffen et al, 2008). In addition to other phenotypes, loss of RBR activity can also prevent fusion of polar nuclei and central cell differentiation (Johnston et al, 2010;Johnston et al, 2008).…”
Section: Wyrd Is Required Postfertilization For Endosperm Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few genes have been shown to be required for both central cell identity and fusion of polar nuclei, e.g. the transcription factors DIANA/AGAMOUS LIKE 61 (DIA/AGL61) and AGL80 (Bemer et al, 2008;Portereiko et al, 2006;Steffen et al, 2008). In addition to other phenotypes, loss of RBR activity can also prevent fusion of polar nuclei and central cell differentiation (Johnston et al, 2010;Johnston et al, 2008).…”
Section: Wyrd Is Required Postfertilization For Endosperm Developmentmentioning
confidence: 99%
“…In Arabidopsis, core components of the splicing machinery are required for the maintenance of gametic versus accessory cell fate (Gross-Hardt et al, 2007;Moll et al, 2008). In addition, central cell fate depends on type I MADS-domain transcription factors (Bemer et al, 2008;Portereiko et al, 2006;Steffen et al, 2008), whereas a MADS target gene is necessary for the differentiation of accessory cells (Matias-Hernandez et al, 2010) and a MYB transcription factor for synergid differentiation (Kasahara et al, 2005). In maize, a LOB-domain transcription factor (Evans, 2007;Guo et al, 2004) and a diSUMO-like protein (Srilunchang et al, 2010) were shown to be involved in embryo sac differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…2 and Table 1) (reviewed by Masiero et al, 2011). For example, the M protein AGL80 and the M protein DIANA (DIA; AGL61) form a functional protein dimer and control the differentiation of the central cell (Portereiko et al, 2006;Bemer et al, 2008;Steffen et al, 2008). AGL80 is also expressed during endosperm development.…”
Section: Gametophyte Embryo and Seed Developmentmentioning
confidence: 99%
“…Furthermore, it is expressed in microspores (Parenicová et al, 2003), but reciprocal crosses excluded a vital role for male gametophyte development. By RT-PCR experiments, AGL80 transcripts were detected in most organs (roots, stems, leaves, flowers, and anthers); therefore, weak alleles or inducible silencing strategies might be useful to shed light on other functions that AGL80 might have during development.Yeast two-hybrid assays showed that AGL80 interacts with the Ma-type MADS domain protein AGL61, named DIANA (DIA; de Folter et al, 2005;Bemer et al, 2008;Steffen et al, 2008). DIA/ AGL61 contains a distinct N-terminal region in front of the MADS domain, thus being different from most of the Ma proteins, where the MADS domain is located close to the N terminus.…”
mentioning
confidence: 99%